1968
DOI: 10.1080/00018736800101346
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear structure studies at medium energies

Abstract: Reactions initiated by electrons, nucleons, pions and kaons in the energy region 100-600 ~ev are discussed. It is shown that valuable information on nuclear structure can be obtained from these reactions, although precise determination of the nucleon momentum distribution in nuclei requires a combined study of a range of reactions and elastic scattering. It is suggested that attempts to determine the nucelon pair correlation function may be premature. CONTENTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
1989
1989

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Proton beams of energy 385 MeV were used at Liverpool to verify the fundamental shell structure of nuclei through the (p,2p) reaction (James er al 1969); figure 11 shows the evidence from this work for bound shells of particles in C. At Harwell the lower energy protons from the synchrocyclotron were used by an Oxford group to excite radiative transitions in nuclei of A up to about 40; it was found that the inelastic scattering picked out states with strong ground state transitions. The use of probes of a few hundred MeV energy in nuclear structure physics was reviewed by Jackson (1968).…”
Section: Nuclear Reactions and Properties (Low-resolution Experiments)mentioning
confidence: 99%
“…Proton beams of energy 385 MeV were used at Liverpool to verify the fundamental shell structure of nuclei through the (p,2p) reaction (James er al 1969); figure 11 shows the evidence from this work for bound shells of particles in C. At Harwell the lower energy protons from the synchrocyclotron were used by an Oxford group to excite radiative transitions in nuclei of A up to about 40; it was found that the inelastic scattering picked out states with strong ground state transitions. The use of probes of a few hundred MeV energy in nuclear structure physics was reviewed by Jackson (1968).…”
Section: Nuclear Reactions and Properties (Low-resolution Experiments)mentioning
confidence: 99%